Probiotics and Atopic Dermatitis: An Overview - Rather, Irfan A.; Bajpai, Vivek K.; Kumar, Sanjay; Lim, Jeongheui; Paek, Woon K.; Park, Yong-Ha (Frontiers in Microbiology, 2016)
Atopic dermatitis (AD) is a common, recurrent, chronic inflammatory skin disease that is a cause of considerable economic and social burden. Its prevalence varies substantially among different countries with an incidence rate proclaimed to reach up to 20% of children in developed countries and continues to escalate in developing nations. This increased rate of incidence has changed the focus of research on AD toward epidemiology, prevention, and treatment. The effects of probiotics in the prevention and treatment of AD remain elusive. However, evidence from different research groups show that probiotics could have positive effect on AD treatment, if any, that depend on multiple factors, such as specific probiotic strains, time of administration (onset time), duration of exposure, and dosage. However, till date we still lack strong evidence to advocate the use of probiotics in the treatment of AD, and questions remain to be answered considering its clinical use in future. Based on updated information, the processes that facilitate the development of AD and the topic of the administration of probiotics are addressed in this review.